Stock Market Panic Cycles Anad Asset Diversification Strategies: The Role of Gold, Foreign Currency, and Bitcoin as Safe Havens in Indonesia - Paulina Harun; Taufiq Pradhana; Batara Maju Simatupang; Antyo Pracoyo (CV. Publikasi Indonesia, 2026)
This research examines the role of gold, foreign exchange, and Bitcoin as hedge, diversifier, and safe haven assets for the Indonesian stock market (IHSG). The study aims to identify alternative investment instruments that can serve as hedging tools, diversifiers, and safe havens during various crisis periods, including the European debt crisis (2011), taper tantrum (2013), China market crisis (2015), COVID-19 pandemic (2020), Russia–Ukraine war (2022), and Middle East geopolitical tensions (2025). Using daily data from July 2011 to December 2025, the analysis covers major crises including the European debt crisis, taper tantrum, COVID-19, the Russia–Ukraine war, and Middle East geopolitical tensions. The study applies Ordinary Least Squares (OLS) with crisis dummy variables and Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH). The findings show that foreign currencies, particularly the US Dollar, consistently function as the strongest safe haven assets for IHSG, followed by the Euro and Chinese Yuan. Gold demonstrates mixed characteristics depending on denomination and form. XAU/USD and ANTAM gold mainly act as diversifiers, while XAU/IDR serves as a weak safe haven due to exchange rate effects. Meanwhile, Bitcoin fails to function as a safe haven and behaves as a speculative risky asset during market crises. The study provides empirical evidence that safe haven characteristics are time-varying and asset-specific, offering practical implications for investment and portfolio diversification strategies, while emphasizing the importance of rupiah exchange rate stability and guiding future research directions.